THE HISTORY OF THE WRITER OYBEK`S HOUSE-MUSEUM IN TASHKENT AND IT`S IMPORTANCE IN THE CULTURAL LIFE OF SOCIETY - Elmuratova Shokhista Ablakulovna (Western European Studies, 2024)
The history of the Oybek House-Museum, which is currently operating in Tashkent, has been studied in the following article. Because most of the existing house-museums in our country aresituated in Tashkent, this paper stresses on studying the history and activities of the house-museums in this region
Keywords: Museum; house-museum; Children's Corner